Hubungan ASI Eksklusif dan Makanan Pendamping ASI (MP ASI) dengan Kejadian Stunting pada Baduta di Wilayah Kerja Puskesmas Singandaru Tahun 2024 - Dini Rachmaniah; Nabila Agustina (NAJ Nursing Applied Journal, 2025)
Stunting is a condition of chronic malnutrition caused by inadequate nutritional intake over a long period of time due to providing food that is not in accordance with nutritional needs. One of the causes of stunting in toddlers is exclusive breastfeeding which is not given for 6 months because breast milk is really needed during the baby's growth period, and it is not appropriate to give complementary foods after 6 months of age so that their nutritional needs are met. This study aims to determine the relationship between exclusive breastfeeding and complementary foods for breastfeeding (MP-ASI) with the incidence of stunting in toddlers in the Singandaru Community Health Center working area in 2024. The research design is descriptive correlation using the case control method. The measuring tool for this research uses a questionnaire. The research results for the exclusive breastfeeding variable based on the chi square test results obtained a value of p = 0.0001, P velocity < α, so Ho is rejected, meaning there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers in the working area of ​​the Singandaru Community Health Center in 2024. As for the complementary food variable ASI (MP ASI) with the incidence of stunting obtained a p value = 0.012, P velue < α, then HO is rejected, the conclusion is that there is a relationship between complementary food for breast milk (MP ASI) and the incidence of stunting in toddlers in the working area of ​​the Singandaru Community Health Center in 2024. Based on research results It is hoped that the cadres can provide motivation to every baduta mother to be able to provide exclusive breast milk and provide complementary breast milk according to her age.